-4+3(18-9m)=

Simple and best practice solution for -4+3(18-9m)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+3(18-9m)= equation:


Simplifying
-4 + 3(18 + -9m) = 0
-4 + (18 * 3 + -9m * 3) = 0
-4 + (54 + -27m) = 0

Combine like terms: -4 + 54 = 50
50 + -27m = 0

Solving
50 + -27m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-50' to each side of the equation.
50 + -50 + -27m = 0 + -50

Combine like terms: 50 + -50 = 0
0 + -27m = 0 + -50
-27m = 0 + -50

Combine like terms: 0 + -50 = -50
-27m = -50

Divide each side by '-27'.
m = 1.851851852

Simplifying
m = 1.851851852

See similar equations:

| x(x+4)+28=(x-1)(x+8) | | 5=6p-1 | | 2x(3x+x^2)-2x^2=136 | | 5=s-6 | | -(x)whenx=8 | | 63x^2-44x=-5x+60 | | j-20=-23 | | -p+4(3p-2)+5= | | (x*5)+21(1-x)=10 | | 16i+z^2=0 | | 123-95=31y-38y | | 36-4x+8=5+5x-1 | | -3(3x-2)+10x-9= | | 123-95=31y-38 | | B-17=(-38) | | 10-3(10-(8+x))=7x-(x-10) | | F(x)=7x^2-37x+5 | | -258=-7(5n-4)-6 | | cosx*cosx*3-sinx*sinx*3=0 | | 3x-5(x-4)=16 | | 6-8x=3x-9 | | t^2-12t+90=0000 | | -x^2-15x+600=0 | | 3.7x+59.8=33-9.7x | | 0.05x+0.07(9000-x)=510 | | x^2-15x+600=0 | | 36=18s | | (2x+10)(2x-7)=342-4x^2 | | z^2=-16i | | .53+.21t=1.09t-.79 | | SQRT(2SQRT(22x+5))=SQRT(5x+4) | | 2+6g=11-3y |

Equations solver categories